Governing the Pandemic The Politics of Navigating a Mega-Crisis - Boin, Arjen (Springer Nature, 2021)
This open access book offers unique insights into how governments and governing systems, particularly in advanced economies, have responded to the immense challenges of managing the coronavirus pandemic and the ensuing disease COVID-19. Written by three eminent scholars in the field of the politics and policy of crisis management, it offers a unique 'bird's eye' view of the immense logistical and political challenges of addressing a worst-case scenario that would prove the ultimate stress test for societies, governments, governing institutions and political leaders. It examines how governments and governing systems have (i) made sense of emerging transboundary threats that have spilled across health, economic, political and social systems (ii) mobilised systems of governance and often fearful and sceptical citizens (iii) crafted narratives amid high uncertainty about the virus and its impact and (iv) are working towards closure and a return to 'normal' when things can never quite be the same again. The book also offers the building blocks of pathways to future resilience. Succeeding and failing in all these realms is tied in with governance structures, experts, trust, leadership capabilities and political ideologies. The book appeals to anyone seeking to understand 'what's going on?', but particularly academics and students across multiple disciplines, journalists, public officials, politicians, non-governmental organisations and citizen groups.